Effect of stress on Parkinsonian Phenotypes in Leucine-rich Repeat Kinase 2 LRRK2 (R1441G) mice mutants - Rahavan, R. (2016)
Parkinson’s disease (PD) is a progressive age related neurodegenerative disorder that affects 13% of the general population above the age of 65. The etiology of Parkinson's is multifactorial and can often involve a variety of factors such as i) genetic mutations and ii) environmental stressors. Pathogenic genetic mutations such as the autosomal dominant R1441G mutation in the Leucine Rich Repeat Kinase 2 gene has been shown to cause phenotypes of late onset PD. We sought to find out if i) the LRRK2 R1441G pathogenic mutation increased the susceptibility towards stress leading to the accelerated onset of parkinsonian phenotypes ii) stress had any effect on the manifestations of key phenotypes in LRRK2 R1441G mice. We performed neurobehavioural tests to assess the motor and nonmotor symptoms at 12 and 16 months. Immunohistochemistry was also performed to analyze the degeneration of dopaminergic neurons in the substantia nigra pars compacta(SNpc). Our results show that the LRRK2 R1441G mutation increased the susceptibility towards stress through the degeneration of dopaminergic neurons and gastrointestinal dysfunction. Stress also significantly accelerated the degeneration of dopaminergic neurons in the SNpc and onset of gastrointestinal dysfunction. However, motor symptoms and depression like behaviour could not be accurately validated due to small sample sizes, ages of the mice used and the need for more accurate neurobehavioural tests.